2015
DOI: 10.2196/jmir.4999
|View full text |Cite
|
Sign up to set email alerts
|

Views of People With High and Low Levels of Health Literacy About a Digital Intervention to Promote Physical Activity for Diabetes: A Qualitative Study in Five Countries

Abstract: BackgroundLow health literacy is associated with poor health-related knowledge, illness self-management, health service use, health, and survival, and thus addressing issues related to low health literacy has been highlighted as a pressing international priority.ObjectiveTo explore views of a digital health promotion intervention designed to be accessible to people with lower levels of health literacy, in particular examining reactions to the interactive and audiovisual elements of the intervention.MethodsQual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 30 publications
4
41
0
3
Order By: Relevance
“…48 There is some evidence that intervention design formats that are accessible and engaging for people with lower levels of health literacy may also be acceptable and usable by people with higher levels. 49 If confirmed, those findings suggest that DBCIs for all can be designed to be accessible and engaging for those with low health literacy. Involving people from lower-income backgrounds in research poses challenges that need to be overcome to better understand their needs and barriers.…”
Section: Promoting Effective Engagementmentioning
confidence: 84%
“…48 There is some evidence that intervention design formats that are accessible and engaging for people with lower levels of health literacy may also be acceptable and usable by people with higher levels. 49 If confirmed, those findings suggest that DBCIs for all can be designed to be accessible and engaging for those with low health literacy. Involving people from lower-income backgrounds in research poses challenges that need to be overcome to better understand their needs and barriers.…”
Section: Promoting Effective Engagementmentioning
confidence: 84%
“…The two in-person interventions improved self-efficacy and glycemic control, and significantly improved HbA1 c and cost savings via the reduction of hospital visits, respectively (Cavanaugh et al, 2009;Micklethwaite, Brownson, O'Toole, & Kilpatrick, 2012). The two Internet interventions were successful in increased confidence and empowerment in individuals to make their own decisions based on knowledge they received, and the ability to use knowledge gained in a way that was beneficial based on their own choices (Long & Gambling, 2011;Rowsell et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…They were born and grew up in an era when the physician's knowledge was unchallenged (Campbell & Nolfi, ; Eger‐Dreyfuss, ) and now find it difficult to accept new norms and understandings developing within the medical community that require patients to take part in the decision making regarding his or her health, and even more so believing that this involvement will have a positive impact on his or her health (Malone, Jo & Clifton, ; Yosephi, ). Research on the health literacy of older people has found that the use of online resources is linked to socio‐economic status, level of education, ethnicity and cognitive ability (Bostock & Steptoe, ; Dhanireddy et al., ; Lyles et al., ; Rowsell et al., ; Sarkar et al., ; Tieu et al., ) and represents a more precise indicator of a patient's pro‐activism (Smith et al., ) alongside to lifelong learning (Bostock & Steptoe, ) in countries such as China (Liu, Liu, Li & Chen, ), Portugal (Veiga & Serrão, ), Britain (Panagioti et al., ; Smith, Jackson, Kobayashi & Steptoe, ), Israel (Mesch, Mano & Tsamir, ), Canada (Couture, Chouinard, Fortin & Hudon, ) and the United States (Hong & Cho, ; Levy et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%